Comparison of Results of Cycles Treated with Modified Mild Protocol and Short Protocol for Ovarian Stimulation. (6th August 2014) - Coelho, F.; Aguiar, L. F.; Cunha, G. S. P.; Cardinot, N.; Lucena, E.
Abstract : The ovarian stimulation has been applied in order to increase the number of oocytes to compensate for the poor results of in vitro fertilization, allowing the selection of one or more embryos to be transferred. Our aim is to compare the results obtained in IVF/ICSI cycles using the short protocol for controlled ovarian stimulation to the results from the modified mild protocol used in our department. A total of 240 cycles were conducted from January 2010 to December 2011. When comparing both protocols, it could be observed that there was a significant difference in the quantity of gonadotropins doses in the mild protocol and in the short protocol. No significant difference was observed regarding pregnancy rates per cycle, 22% and 26.2%, in short and mild protocols, respectively. The protocols of controlled ovarian stimulation are often associated with high risk of complications such as ovarian hyperstimulation syndrome, excessive emotional stress, high rates of treatment dropouts, and abdominal discomfort. With the data obtained in this study, one can conclude that there are less risks and complications for the patient when using the mild stimulation protocol. It was also observed that in this group there was a slightly higher rate.